Gold for bronze (χρύσεα χαλκείων): a Greek paroimia turned into an epistolary topos during the European Renaissance - Míguez Lamanuzzi, Marina (Romanica Olomucensia, 2025)
The aim of this paper is to study χρύσεα χαλκείων 'gold for bronze', a Greek paroimia found in Homer's Iliad. The mechanisms by which this Homeric verse became a proverb will be analysed, such as its use in numerous passages by classical Greek and Latin authors, as well as intellectuals of the European Renaissance, particularly in their correspondence. With regard to the methodology, the methods pertaining to the field of Classical Philology have been employed. An exhaustive study of the texts from both a synchronic and a diachronic point of view was conducted, taking into account all the textual variants and their context. The results of this analysis have contributed to a deeper understanding of the history of this paroimia, from its origins in Greek oral literature to the present day. Indeed, it can still be observed in several modern languages, mainly Spanish, Italian, and French. Furthermore, the study of this paroimia has also allowed us to identify and explain the development of its multiple variants, as well as to understand the specific contexts of its use. In conclusion, this study underscores the importance of researching ancient Greek paroimiai as a gateway to understanding the development of modern European cultures, languages, and literatures. Many paroimiai coined by the ancients survive nowadays and are a testament to the substantial unity of European culture stemming from its Greek and Roman roots.
Keywords: ancient paremiology; epistolography; Iliad; Angelo Poliziano; Erasmus of